Directional heat-conducting composite glass and its preparation method and application

By injecting graphene oxide water dispersion into the window glass of the surveillance camera and performing laser array irradiation, the problem of fogging or freezing in the window at extremely low temperatures is solved, and the direction of efficient thermal conductivity and high transmittance is achieved Thermal composite glass.

CN116495979BActive Publication Date: 2025-02-14ZHEJIANG DAHUA TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310288859.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-21
Publication Date
2025-02-14
Estimated Expiration
2043-03-21

AI Technical Summary

Technical Problem

In extremely low temperature environments, the windows of the surveillance camera equipment are prone to fog or icing, resulting in unclear images, and existing thermal glasses will affect the transmittance when improving thermal conductivity.

Method used

By adopting a preparation method of directional thermal conduction composite glass, the uniform dispersion of graphene oxide and the construction of directional thermal conduction structure is achieved by injecting the aqueous dispersion of graphene into the glass liquid and irradiating laser array.

Benefits of technology

It realizes the high thermal conductivity and thermal uniformity of directional thermal conductivity composite glass, while maintaining a high overall transmittance. It is suitable for camera windows and can effectively realize the self-defog and defrost function.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to a directional heat-conducting composite glass and a preparation method and application thereof. The preparation method of the directional heat-conducting composite glass comprises the following steps: melting glass powder to form glass liquid; placing the glass liquid in a molding device for molding, and injecting graphene oxide aqueous dispersion from the bottom of the molding device into the glass liquid to form a mixture, and the mixture is cooled and solidified to obtain a pre-treated composite glass; subjecting the pre-treated composite glass to laser array irradiation treatment to obtain a directional heat-conducting composite glass, wherein in the step of laser array irradiation treatment, the laser wavelength energy is less than the electron transition energy of graphene oxide. The preparation method can make the graphene dispersed evenly and conduct heat in a directional manner, and at the same time make the obtained directional heat-conducting composite glass have a higher overall transmittance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat-conducting material preparation, and in particular to a directional heat-conducting composite glass and a preparation method and application thereof. Background Art

[0002] Surveillance cameras are placed in extremely low outdoor temperature environments, such as in cold regions such as northern my country, Northern Europe, and North America. Due to differences in ambient temperature and humidity, the windows will fog or freeze, resulting in unclear images, affecting the surveillance effect, and even causing the surveillance cameras to be unusable in severe cases. To this end, it is necessary to achieve the self-defogger and defrost function of the windows by heating and other means. The intrinsic thermal conductivity of the glass used for windows is low, and using it in heat-conducting devices will seriously affect the heat transfer efficiency. Although it can be improved to a certain extent by filling with high thermal conductivity particles, in order to effectively improve the thermal conductivity, a large amount of high thermal conductivity particles need to be added. However, an excessively high ratio of high thermal conductivity particles will significantly affect the transmittance of the glass itself.

[0003] Graphene has excellent electrical and thermal conductivity. Using it as a filling material to prepare graphene glass composites is beneficial to improving the thermal conductivity of graphene glass composites. However, graphene cannot be evenly dispersed in the glass liquid, resulting in problems such as uneven thermal conductivity in graphene glass composites. Summary of the invention

[0004] Based on this, it is necessary to provide a directional heat-conducting composite glass and its preparation method and application to address the above problems; the preparation method can make the graphene dispersed evenly and conduct heat in a directional manner, and at the same time make the prepared directional heat-conducting composite glass have a higher overall transmittance.

[0005] A method for preparing directional heat-conducting composite glass comprises the following steps:

[0006] Melting glass powder to make molten glass;

[0007] The glass liquid is placed in a molding device for molding, and at the same time, a graphene oxide aqueous dispersion is injected into the glass liquid from the bottom of the molding device to form a mixture, and the mixture is cooled and solidified to obtain a pretreated composite glass; and

[0008] The pretreated composite glass is subjected to laser array irradiation treatment to obtain a directional heat-conducting composite glass, wherein in the step of laser array irradiation treatment, the laser wavelength energy is less than the electron transition energy of graphene oxide.

[0009] In one embodiment, the melting temperature is 1000°C-1300°C.

[0010] In one embodiment, in the step of injecting the graphene oxide aqueous dispersion into the glass liquid from the bottom of the molding device to form a mixture, the injection pressure is 0.3MPa-0.5MPa.

[0011] In one of the embodiments, the injection position of the graphene oxide aqueous dispersion coincides with the center point of the bottom of the molding device.

[0012] In one embodiment, the mass fraction of the graphene oxide aqueous dispersion in the mixture is 15%-20%.

[0013] In one of the embodiments, in the graphene oxide aqueous dispersion, the mass ratio of graphene oxide to water is 2:1-3:1.

[0014] In one embodiment, in the step of laser array irradiation treatment, the laser wavelength is 518nm-637nm, and the power density is 350mW / mm 2 -390mW / mm 2 , the time is 20min-30min.

[0015] In one of the embodiments, in the step of laser array irradiation treatment, the spot diameter of the laser array irradiation is 50µm-100µm, and the spot spacing is 300µm-600µm.

[0016] A directional heat-conducting composite glass prepared by the method for preparing the directional heat-conducting composite glass as described above.

[0017] The directional heat-conducting composite glass as described above is applied to a camera window.

[0018] The method for preparing the directional heat-conducting composite glass of the present invention has the following beneficial effects:

[0019] First, when the graphene oxide aqueous dispersion is sprayed into the glass liquid from the bottom of the molding device for mixing, since the graphene oxide aqueous dispersion and the glass liquid are both in liquid state and the density of the graphene oxide aqueous dispersion is lower than that of the glass liquid, the dispersion effect of the graphene oxide in the glass liquid can be improved by utilizing the dispersion principle of low-density liquid in high-density liquid and the buoyancy of ultra-light graphene oxide; second, since the glass liquid itself has a high temperature, the rapid increase of water in the graphene oxide aqueous dispersion can further promote the separation of graphene oxide, thereby further improving the dispersion effect of graphene oxide; third, the glass liquid is The speed of cooling in the air to form amorphous is very fast, and the overall solidification can be achieved before the graphene oxide re-aggregates, so that the graphene oxide can be evenly distributed in the pre-treated composite glass; Fourth, when the laser with a specific wavelength energy is used for array irradiation treatment, the graphene oxide can be reduced, and the reduced graphene oxide can be distributed in a directional manner to construct a directional heat conduction structure. At the same time, the use of laser for array irradiation treatment can soften the local glass, eliminate the water vapor and carbon dioxide generated during the reduction of graphene oxide, increase the single-layer spacing of graphene, and thus improve the overall transmittance of the directional heat conduction composite glass.

[0020] Therefore, the directional thermal conductive composite glass obtained by the preparation method of the present invention not only has high thermal conductivity and uniform thermal conductivity, but also has high overall transmittance. Furthermore, the directional thermal conductive composite glass of the present invention is used for camera windows to better realize the self-defrosting and defrosting functions. DETAILED DESCRIPTION

[0021] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0023] The present invention provides a method for preparing a directional heat-conducting composite glass, comprising the following steps:

[0024] S1, melting glass powder to form glass liquid;

[0025] S2, placing the glass liquid in a molding device for molding, and injecting graphene oxide aqueous dispersion from the bottom of the molding device into the glass liquid to form a mixture, and the mixture is cooled and solidified to obtain a pretreated composite glass; and

[0026] S3, subjecting the pretreated composite glass to laser array irradiation treatment to obtain directional thermal conductive composite glass, wherein in the step of laser array irradiation treatment, the laser wavelength energy is less than the electron transition energy of graphene oxide.

[0027] In step S1, the melting temperature is preferably 1000°C-1300°C, which can make the viscosity of the molten glass 10Pa·s-100Pa·s, which is beneficial to improve the injection effect of the graphene oxide aqueous dispersion, and further improve the dispersion effect of graphene oxide in the glass liquid.

[0028] Specifically, the present invention does not limit the type of glass powder, and the glass powder includes but is not limited to at least one of silicate glass powder, borate glass powder, and phosphate glass powder, preferably silicate glass powder.

[0029] In step S2, when the graphene oxide aqueous dispersion is sprayed into the glass liquid from the bottom of the molding device for mixing, since the graphene oxide aqueous dispersion and the glass liquid are both in liquid state, and the density of the graphene oxide aqueous dispersion is lower than that of the glass liquid, the dispersion principle of low-density liquid in high-density liquid and the buoyancy of ultra-light graphene oxide can be used to improve the dispersion effect of graphene oxide in the glass liquid. In addition, since the glass liquid itself has a high temperature, when the water in the graphene oxide aqueous dispersion increases rapidly, the separation of graphene oxide can be further promoted, thereby further improving the dispersion effect of graphene oxide.

[0030] At the same time, the glass liquid cools in the air to form amorphous materials very quickly, and the overall solidification can be achieved before the graphene oxide reaggregates. In addition, since the surface of the glass liquid away from the bottom of the molding device solidifies first, it can also ensure that the graphene oxide dispersed to the surface due to buoyancy will not reaggregate, thereby allowing the graphene oxide to be evenly distributed in the pretreated composite glass.

[0031] In addition, since the glass liquid itself has a relatively high temperature, a small amount of graphene oxide may be reduced while the graphene oxide is dispersed. However, the glass liquid injected with graphene oxide can achieve effects such as air isolation, without the need to set up an additional protective gas atmosphere, and can also ensure that part of the reduced graphene oxide will not be re-oxidized by oxygen in the air.

[0032] In the step of injecting the graphene oxide aqueous dispersion from the bottom of the molding device into the glass liquid to form a mixture, the injection pressure is preferably 0.3MPa-0.5MPa, which is conducive to improving the injection effect of the graphene oxide aqueous dispersion, and then improving the dispersion effect of graphene oxide in the glass liquid.

[0033] It should be noted that the present invention does not limit the specific injection method of the graphene oxide aqueous dispersion. The graphene oxide aqueous dispersion can be injected after the glass liquid is completely poured into the molding device; or the graphene oxide aqueous dispersion can be injected during the process of pouring the glass liquid into the molding device. Similarly, the present invention does not limit the injection completion time of the graphene oxide aqueous dispersion. The pouring of the glass liquid can be completed first and then the injection of the graphene oxide aqueous dispersion, or the injection of the graphene oxide aqueous dispersion can be completed first and then the pouring of the glass liquid. Those skilled in the art can design it according to actual preparation requirements.

[0034] The present invention does not limit the specific injection position of the graphene oxide aqueous dispersion. The injection port can be at any position on the bottom of the glass liquid forming device, and those skilled in the art can adjust the injection port to a certain angle according to the actual preparation situation.

[0035] In order to ensure that the graphene oxide aqueous dispersion has the best dispersion effect during injection, preferably, the injection position of the graphene oxide aqueous dispersion coincides with the center point of the bottom of the glass liquid forming device, and more preferably, the graphene oxide aqueous dispersion is injected vertically upward from the center point of the bottom of the forming device.

[0036] It should be noted that when the bottom of the glass liquid forming device is an irregular shape, the balance point of the irregular shape is the center point.

[0037] In order to facilitate the injection of the graphene oxide aqueous dispersion from the bottom of the glass liquid molding device, in one embodiment, before the glass liquid is placed in the molding device for molding, a quartz tube can be inserted into the bottom of the molding device to allow the graphene oxide aqueous dispersion to be injected into the glass liquid from the quartz tube.

[0038] Preferably, the mass fraction of the graphene oxide aqueous dispersion in the mixture is 15%-20%, which is beneficial for maintaining a high transmittance of the composite glass.

[0039] In order to reduce the agglomeration of graphene oxide in the graphene oxide aqueous dispersion and at the same time ensure that the amount of graphene oxide dispersed in the directional thermal conductive composite glass can achieve a better thermal conductive effect, in the graphene oxide aqueous dispersion, the mass ratio of graphene oxide to water is preferably 2:1-3:1.

[0040] Wherein, the water in the graphene oxide aqueous dispersion is preferably deionized water.

[0041] Step S3, when a laser with a specific wavelength energy is used for array irradiation treatment, the graphene oxide within the laser array irradiation range absorbs more photons and generates high temperature, so that the chemical bonds of the functional groups on the surface of the graphene oxide are broken to achieve photothermal reduction, and the obtained reduced graphene oxide can be distributed in a directional manner to construct a directional heat conduction structure. At the same time, the high temperature generated by the laser array irradiation treatment can soften the local glass, remove the water vapor and carbon dioxide generated during the reduction of the graphene oxide, increase the single-layer spacing of the graphene, and thus improve the overall transmittance of the directional heat conduction composite glass.

[0042] It should be noted that, due to the regular arrangement of the laser array, on the one hand, it is conducive to forming a uniformly distributed directional heat conduction structure, thereby further promoting uniform heat conduction of the directional heat conduction composite glass; on the other hand, it can make the directional heat conduction composite glass have uniform transmittance.

[0043] Preferably, the laser wavelength is 518nm-637nm.

[0044] Optionally, the power density of the laser array irradiation is 350 mW / mm 2 -390mW / mm 2 , the time is 20min-30min.

[0045] In one embodiment, in the step of laser array irradiation treatment, the laser irradiation array is preferably designed with a spot diameter of 50µm-100µm and a spot spacing of 300µm-600µm.

[0046] The present invention provides a directional heat-conducting composite glass prepared by the method for preparing the directional heat-conducting composite glass as described above.

[0047] The directional heat-conducting composite glass of the present invention not only has high thermal conductivity and uniform heat conduction, but also has high overall transmittance, and can be used for the heat-conducting glass layer in devices such as heaters.

[0048] The present invention also provides an application of the directional heat-conducting composite glass in a camera window.

[0049] The directional heat-conducting composite glass of the present invention has excellent heat-conducting effect when used for camera windows, can enable the camera windows to achieve self-defog and defrost functions, and is particularly suitable for outdoor low-temperature working environments.

[0050] Hereinafter, the directional heat-conducting composite glass and its preparation method and application will be further described through the following specific examples.

[0051] Example 1

[0052] The silicate glass powder is softened and melted at 1300°C to obtain a silicate glass liquid with a viscosity of 10 Pa·s.

[0053] Graphene oxide and deionized water are mixed and dispersed uniformly in a mass ratio of 2:1 to obtain a graphene oxide aqueous dispersion. A quartz tube is inserted into the center point of the bottom of a molding device, and while the silicate glass liquid is poured into the molding device for plane molding, the graphene oxide aqueous dispersion is vertically injected into the glass liquid along the quartz tube from the center point of the bottom of the molding device under an injection pressure of 0.3 MPa to form a mixture, wherein the mass fraction of the graphene oxide aqueous dispersion in the mixture is 20%. After the mixture is cooled and solidified in air, a pretreated composite glass is obtained.

[0054] The laser source with a wavelength of 518nm is used at 360mW / mm 2 Under the condition of power density of , the pretreated composite glass was irradiated with a spot array with a diameter of 50µm and a spacing of 300µm for 30 minutes to obtain a directional heat-conducting composite glass.

[0055] Example 2

[0056] The silicate glass powder was softened and melted at 1150°C to obtain a silicate glass liquid with a viscosity of 50 Pa·s.

[0057] Graphene oxide and deionized water are mixed and dispersed uniformly in a mass ratio of 2:1 to obtain a graphene oxide aqueous dispersion. A quartz tube is inserted into the center point of the bottom of a molding device, and while a silicate glass liquid is poured into the molding device for plane molding, the graphene oxide aqueous dispersion is vertically injected into the glass liquid along the quartz tube from the center point of the bottom of the molding device under an injection pressure of 0.4 MPa to form a mixture, wherein the mass fraction of the graphene oxide aqueous dispersion in the mixture is 20%. After the mixture is cooled and solidified in air, a pretreated composite glass is obtained.

[0058] The laser source with a wavelength of 518nm and a power of 360mW / mm 2 Under the condition of power density of , the pretreated composite glass was irradiated with a spot array with a diameter of 50µm and a spacing of 300µm for 30 minutes to obtain a directional heat-conducting composite glass.

[0059] Example 3

[0060] The silicate glass powder is softened and melted at 1000°C to obtain a silicate glass liquid with a viscosity of 100 Pa·s.

[0061] Graphene oxide and deionized water are mixed and dispersed uniformly in a mass ratio of 2:1 to obtain a graphene oxide aqueous dispersion. A quartz tube is inserted into the bottom right position of a molding device, and while the silicate glass liquid is poured into the molding device for plane molding, the graphene oxide aqueous dispersion is injected into the glass liquid along the quartz tube in an upper left direction under an injection pressure of 0.5 MPa to form a mixture, wherein the mass fraction of the graphene oxide aqueous dispersion in the mixture is 20%. After the mixture is cooled and solidified in air, a pretreated composite glass is obtained.

[0062] The laser source with a wavelength of 518nm and a power of 360mW / mm 2 Under the condition of power density of , the pretreated composite glass was irradiated with a spot array with a diameter of 50µm and a spacing of 300µm for 30 minutes to obtain a directional heat-conducting composite glass.

[0063] Example 4

[0064] The silicate glass powder is softened and melted at 1300°C to obtain a silicate glass liquid with a viscosity of 10 Pa·s.

[0065] Graphene oxide and deionized water are mixed and dispersed uniformly in a mass ratio of 2:1 to obtain a graphene oxide aqueous dispersion. A quartz tube is inserted into the center point of the bottom of a molding device, and while the silicate glass liquid is poured into the molding device for plane molding, the graphene oxide aqueous dispersion is vertically injected into the glass liquid along the quartz tube from the center point of the bottom of the molding device under an injection pressure of 0.3 MPa to form a mixture, wherein the mass fraction of the graphene oxide aqueous dispersion in the mixture is 20%. After the mixture is cooled and solidified in air, a pretreated composite glass is obtained.

[0066] The laser source has a wavelength of 637nm and a power of 390mW / mm 2 Under the condition of power density of , the pretreated composite glass was irradiated with a spot array with a diameter of 80µm and a spacing of 500µm for 20min to obtain a directional heat-conducting composite glass.

[0067] Example 5

[0068] The silicate glass powder is softened and melted at 1300°C to obtain a silicate glass liquid with a viscosity of 10 Pa·s.

[0069] Graphene oxide and deionized water are mixed and dispersed uniformly in a mass ratio of 2:1 to obtain a graphene oxide aqueous dispersion. A quartz tube is inserted into the center point of the bottom of a molding device, and while the silicate glass liquid is poured into the molding device for plane molding, the graphene oxide aqueous dispersion is vertically injected into the glass liquid along the quartz tube from the center point of the bottom of the molding device under an injection pressure of 0.3 MPa to form a mixture, wherein the mass fraction of the graphene oxide aqueous dispersion in the mixture is 20%. After the mixture is cooled and solidified in air, a pretreated composite glass is obtained.

[0070] The laser source with a wavelength of 518nm is used at 350mW / mm 2 Under the condition of power density of , the pretreated composite glass was irradiated with a spot array with a diameter of 100µm and a spacing of 600µm for 25min to obtain a directional heat-conducting composite glass.

[0071] Example 6

[0072] The borate glass powder is softened and melted at 1300°C to obtain a borate glass liquid with a viscosity of 10 Pa·s.

[0073] Graphene oxide and deionized water are mixed and dispersed uniformly at a mass ratio of 3:1 to obtain a graphene oxide aqueous dispersion. A quartz tube is inserted into the center point of the bottom of a molding device, and while the borate glass liquid is poured into the molding device for plane molding, the graphene oxide aqueous dispersion is vertically injected into the glass liquid along the quartz tube from the center point of the bottom of the molding device under an injection pressure of 0.3 MPa to form a mixture, wherein the mass fraction of the graphene oxide aqueous dispersion in the mixture is 15%. After the mixture is cooled and solidified in air, a pretreated composite glass is obtained.

[0074] The laser source with a wavelength of 518nm is used at 360mW / mm 2 Under the condition of power density of , the pretreated composite glass was irradiated with a spot array with a diameter of 50µm and a spacing of 300µm for 30 minutes to obtain a directional heat-conducting composite glass.

[0075] Comparative Example 1

[0076] Graphene oxide and silicate glass powder are directly mixed and ground in a mass ratio of 1:4 to obtain a mixed powder. The mixed powder is softened and melted at 1300°C to obtain a mixed glass liquid with a viscosity of 10 Pa·s. The mixed glass liquid is poured into a molding device for plane molding, and after cooling and solidification in air, a pretreated composite glass is obtained.

[0077] The laser source with a wavelength of 518nm is used at 360mW / mm 2Under the condition of power density of , the pretreated composite glass was irradiated with a spot array with a diameter of 50µm and a spacing of 300µm for 30 minutes to obtain a directional heat-conducting composite glass.

[0078] Comparative Example 2

[0079] The difference between Comparative Example 2 and Example 1 is that the graphene oxide aqueous dispersion is injected into the glass liquid from the center point of the top of the molding device.

[0080] Comparative Example 3

[0081] The difference between Comparative Example 3 and Example 1 is that the silicate glass liquid is poured into the molding device and semi-cured for 5 minutes before being injected with the graphene oxide aqueous dispersion.

[0082] Comparative Example 4

[0083] The difference between Comparative Example 4 and Example 1 is that the pretreated composite glass is array-irradiated with a laser having a wavelength of 351 nm, and the laser energy of this wavelength is higher than the electron transition energy of graphene oxide.

[0084] The directional heat-conducting composite glasses prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were subjected to performance tests, and ordinary silicate glass was used as a blank control group. The test results are shown in Table 1.

[0085]

[0086] According to Table 1, the directional heat-conducting composite glasses prepared in Examples 1 to 6 have excellent thermal conductivity and transmittance. In Comparative Example 1, graphene oxide and silicate glass powder are directly mixed to form glass liquid, resulting in uneven dispersion of graphene oxide, which affects the thermal conductivity and transmittance of the composite glass; in Comparative Example 2, the graphene oxide aqueous dispersion is injected from the top of the molding device, so that the graphene oxide is only distributed on one side of the molded glass, resulting in poor thermal conductivity of the composite glass, and also has an adverse effect on its transmittance; in Comparative Example 3, the dispersion is injected after semi-solidification, resulting in the aggregation of graphene oxide and difficulty in dispersion, which reduces the thermal conductivity and transmittance of the composite glass; in Comparative Example 4, the wavelength energy of the 351nm light source is too high, although the graphene oxide can be reduced, but the long-term laser irradiation causes the internal temperature to be too high, which damages the glass to a certain extent, thereby significantly affecting the transmittance of the composite glass.

[0087] Application Example 1

[0088] A silver nanowire transparent film with a square resistance of 30Ω / □ was attached to the surface of the directional heat-conducting composite glass prepared in Example 1, and used for the camera window after defoaming.

[0089] Under the condition of 12V DC output voltage, the surface temperature of the camera window rises to 69°C within 20s.

[0090] Application Example 2

[0091] A silver nanowire transparent film with a square resistance of 30Ω / □ was attached to the surface of the directional heat-conducting composite glass prepared in Example 2, and used for the camera window after defoaming.

[0092] Under the condition of 12V DC output voltage, the surface temperature of the camera window rises to 70°C within 18s.

[0093] Application Example 3

[0094] A silver nanowire transparent film with a square resistance of 30Ω / □ was attached to the surface of the directional heat-conducting composite glass prepared in Example 3, and used for the camera window after defoaming.

[0095] Under the condition of 12V DC output voltage, the surface temperature of the camera window rises to 68°C within 25s.

[0096] Application Example 4

[0097] A silver nanowire transparent film with a square resistance of 30Ω / □ was attached to the surface of the directional heat-conducting composite glass prepared in Example 4, and used for the camera window after defoaming.

[0098] Under the condition of 12V DC output voltage, the surface temperature of the camera window rises to 68°C within 23s.

[0099] Application Example 5

[0100] A silver nanowire transparent film with a square resistance of 30Ω / □ was attached to the surface of the directional heat-conducting composite glass prepared in Example 5, and used for the camera window after defoaming.

[0101] Under the condition of 12V DC output voltage, the surface temperature of the camera window rises to 68°C within 25s.

[0102] Application Example 6

[0103] A silver nanowire transparent film with a square resistance of 30Ω / □ was attached to the surface of the directional heat-conducting composite glass prepared in Example 6, and used for the camera window after defoaming.

[0104] Under the condition of 12V DC output voltage, the surface temperature of the camera window rises to 70°C within 17s.

[0105] Application Comparative Example 1

[0106] A silver nanowire transparent film with a square resistance of 30Ω / □ was attached to the surface of the directional heat-conducting composite glass prepared in Comparative Example 1, and used for a camera window after defoaming.

[0107] Under the condition of 12V DC output voltage, the surface temperature of the camera window rises to 63°C within 56s.

[0108] Application Comparative Example 2

[0109] A silver nanowire transparent film with a square resistance of 30Ω / □ was attached to the surface of the directional heat-conducting composite glass prepared in Comparative Example 2, and used for a camera window after defoaming.

[0110] Under the condition of 12V DC output voltage, the surface temperature of the camera window rises to 64°C within 48s.

[0111] Application Comparative Example 3

[0112] A silver nanowire transparent film with a square resistance of 30Ω / □ was attached to the surface of the directional heat-conducting composite glass prepared in Comparative Example 3, and used for the camera window after defoaming.

[0113] Under the condition of 12V DC output voltage, the surface temperature of the camera window rises to 63°C within 55s.

[0114] Application Comparative Example 4

[0115] A silver nanowire transparent film with a square resistance of 30Ω / □ was attached to the surface of the directional heat-conducting composite glass prepared in Comparative Example 4, and used for a camera window after defoaming.

[0116] Under the condition of 12V DC output voltage, the surface temperature of the camera window rises to 69°C within 20s.

[0117] Blank control group

[0118] A silver nanowire transparent film with a square resistance of 30Ω / □ is bonded to the surface of ordinary silicate glass and used as a camera window after defoaming.

[0119] Under the condition of 12V DC output voltage, the temperature rise of the camera window reaches 59°C within 2 minutes.

[0120] By comparing Application Example 1 to Application Example 6, Application Comparative Example 1 to Application Comparative Example 4 and the blank control group, it can be seen that the directional heat-conducting composite glass prepared by the present solution has an excellent heat-conducting effect when used in the camera window.

[0121] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0122] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a directional heat-conducting composite glass, characterized in that: The preparation method comprises the following steps: Melting glass powder to make molten glass; The glass liquid is placed in a molding device for molding, and at the same time, a graphene oxide aqueous dispersion is injected into the glass liquid from the bottom of the molding device to form a mixture, and the mixture is cooled and solidified to obtain a pretreated composite glass; and The pretreated composite glass is subjected to laser array irradiation treatment to obtain a directional thermal conductive composite glass, wherein in the step of laser array irradiation treatment, the laser wavelength energy is less than the electron transition energy of graphene oxide.

2. The method for preparing the directional heat-conducting composite glass according to claim 1, characterized in that: The melting temperature is 1000°C-1300°C.

3. The method for preparing the directional heat-conducting composite glass according to claim 1, characterized in that: In the step of injecting the graphene oxide aqueous dispersion from the bottom of the molding device into the glass liquid to form a mixture, the injection pressure is 0.3MPa-0.5MPa.

4. The method for preparing the directional heat-conducting composite glass according to claim 1, characterized in that: The injection position of the graphene oxide aqueous dispersion coincides with the center point of the bottom of the molding device.

5. The method for preparing directional heat-conducting composite glass according to claim 1, characterized in that: The mass fraction of the graphene oxide aqueous dispersion in the mixture is 15%-20%.

6. The method for preparing directional heat-conducting composite glass according to claim 1, characterized in that: In the graphene oxide aqueous dispersion, the mass ratio of graphene oxide to water is 2:1-3:

1.

7. The method for preparing directional heat-conducting composite glass according to claim 1, characterized in that: In the step of laser array irradiation treatment, the laser wavelength is 518nm-637nm, and the power density is 350mW / mm 2 -390mW / mm 2 , the time is 20min-30min.

8. The method for preparing directional heat-conducting composite glass according to claim 1, characterized in that: In the step of laser array irradiation treatment, the spot diameter of the laser array irradiation is 50µm-100µm, and the spot spacing is 300µm-600µm. 9 . A directional heat-conducting composite glass prepared by the method for preparing a directional heat-conducting composite glass according to any one of claims 1 to 8 .

10. The directional heat-conducting composite glass according to claim 9 is applied to a camera window.

Citation Information

Patent Citations

  • Method for preparing composite glass fibers coated with graphene

    CN110218001A

  • Preparation method of optical fiber NV color center single / multi-photon source

    CN110510885A